Factors that influence the total units of container throughput in Penang Port Sdn Bhd / Mohd Afif Mohd Rusi @ Mohd Radzi (Faculty of Business and Management, 2007)
This study was conducted to examine the factors that influence the total units of container throughput in Penang Port Sdn Bhd. In this study, it will be revealed on the factors that influence the total units of container throughput such as number of vessels, number of train and exchange rate. Pile objective of this research is to analyze whether there are any relationship between the number of vessels call at port, number of train and exchange rate with the total units of container throughput in Penang Port Sdn Bhd. This study uses secondary data that have been gathered from the Penang Port Sdn Bhd. itself and also website such as Bank Negara Malaysia. Then, the data were analyzed using Statistical Package for Social Science (SPSS) software. This study comes out with hypotheses to analyze the relationship between independent variables and dependent variable. After the finding has been done, the independent variables on the number of vessels and number of train have significant relationship with the total units of container through put in Penang Port Sdn Bhd. While the exchange rate variable had no significant relationship with the total units of container through in Penang Port Sdn. Bhd. Hopefully, the findings of this research can give some reference to the organizations and also researcher.